Standardization of Broth Microdilution and Disk Diffusion Susceptibility Tests for Actinobacillus pleuropneumoniae and Haemophilus somnus: Quality Control Standards for Ceftiofur, Enrofloxacin, Florfenicol, Gentamicin, Penicillin, Tetracycline, Tilmicosin, and Trimethoprim-Sulfamethoxazole - McDermott, P. F. (American Society for Microbiology, 2001)
Quality control (QC) standards for the in vitro antimicrobial susceptibility testing of two fastidious veterinary pathogens, Actinobacillus pleuropneumoniae and Haemophilus somnus, were developed in a multilaboratory study according to procedures established by the National Committee for Clinical Laboratory Standards for broth microdilution and disk diffusion testing. The medium recommended for the broth microdilution testing is cation-adjusted Mueller-Hinton broth supplemented with 2% lysed horse blood, 2% yeast extract, and 2% supplement C. This medium has been designated veterinary fastidious medium. The medium recommended for the disk diffusion testing is chocolate Mueller-Hinton agar. The recommended QC organisms are A. pleuropneumoniae ATCC 27090 and H. somnus ATCC 700025. The QC MICs of ceftiofur, enrofloxacin, florfenicol, gentamicin, penicillin, tetracycline, tilmicosin, and trimethoprim-sulfamethoxazole were determined for each isolate, as were the zone size ranges. Of the results from the participating laboratories, 94.0% of the zone diameter results and 97.0% of the MIC results fell within the suggested QC ranges for all compounds. These QC guidelines should allow greater accuracy in interpreting results when testing these antimicrobial agents against fastidious pathogens.